THE CAPITAL STRUCTURE OF VENTURE CAPITAL FIRMS IN INDONESIA - Andi Buchari; Noer Azam Achsani; Mangara Tambunan; Tubagus Nur Ahmad Maulana (Jurnal Keuangan dan Perbankan, 2016)
Venture capital (VC) is an important fund source for small and medium enterprises (SMEs) and start up, particularly to deliver its main product of equity participation. Therefore, capital structure and factors that affect it are very crucial. This study aims to analyze the capital structure of VC firms in Indonesia using econometric model of panel data regression. This study utilizes secondary data of six years period (2009-2014) monthly financial statements of 27 samples out of 58 VC firms to form 1,944 observations. The study reveals that capital structure of VC firms in Indonesia is dominated by debt/loan rather than capital with DER on average is 136.95%. In addition, the research confirms that VC firms capital structure is affected simultaneously by financial aspects which are asset size, profitability, liquidity, asset/investment quality, and earning asset structure. The attentions to financial aspects that affect the VC firms capital structure as well as other initiatives related to capital increases are necessary so that the VC firms could carry out its role effectively.